(untitled) (Research, Society and Development, 2024)
Objective: to report the experience of developing a class on patient safety for a group of residents, facing an adverse event, from the use of active teaching methodologies and Bloom Taxonomy. Methodology: this is a descriptive study, the type of experience report, developed from a class that addressed the protocol of safe administration of medication for a group of 20 nursing residents of a university hospital located in southern Brazil. The inverted classroom methodology was used, in which residents received the protocol of safe administration of medication previously. From teaching strategies, we used the lecture dialogue, Problem-Based Learning and the mini-seminar. Results: a real case, of public knowledge, was presented, which dealt with adverse event related to medication error. Subsequently, there was the proposal to prepare the Ishikawa diagram and action plan based on the 5W2H model. For the evaluation of the results achieved, Bloom’s Taxonomy was used, which allowed to recognize that the cognitive and affective domains were achieved. Conclusion: the use of active teaching methodologies and Bloom’s Taxonomy in the residency classes can be considered an effective pedagogical strategy, encouraging the protagonism and autonomy of residents in the teaching-learning process. In addition, it enabled the insertion and discussion of the subject of patient safety in the context of health education.